The relationship between empowerment and stigma among the Chinese people with diabetes: the mediating role of self-management and the moderating role of psychological resilience - Mei, Yujin; Zhang, Lin; Zhang, Fuying; Shen, Yalin; Chen, Mingjia; Guo, Hui (Frontiers in Psychology, 2026)
BackgroundDiabetes mellitus is highly prevalent in China, and individuals affected by this condition often experience stigma, which negatively impacts their psychological well-being and disease management. Empowerment interventions have the potential to reduce stigma by enhancing patients’ knowledge and skills; however, the mechanisms underlying this effect are not yet fully understood. The present study aimed to examine the mediating role of self-management behaviors and the moderating effect of psychological resilience (PR) in this context.MethodThis study employed a cross-sectional design and included 329 individuals with diabetes, selected through a multistage stratified sampling method. Data collection instruments comprised the diabetes empowerment scale, the Connor-Davidson resilience scale, the stigma scale for chronic illness, and the diabetes management self-efficacy scale. Statistical analyses were performed using SPSS version 23.0, alongside the PROCESS macro, to investigate mediating and moderated mediation effects.ResultsEmpowerment (r = −0.451, p < 0.001), self-management (r = −0.397, p < 0.001), and PR (r = −0.325, p < 0.001) each demonstrated significant negative correlations with stigma. Furthermore, self-management was found to partially mediate the association between empowerment and stigma, accounting for 45.44% of the total effect [β = −0.169, 95% CI (−0.272, −0.088)]. PR significantly moderated the relationship between empowerment and self-management (β = 0.002, p < 0.001), as well as the direct relationship between empowerment and stigma (β = −0.012, p < 0.001). Simple slope analyses revealed that the positive influence of empowerment on self-management and the negative influence of empowerment on stigma were both more pronounced among individuals exhibiting higher levels of PR.ConclusionOur study demonstrates that empowerment has a direct impact on the stigma experienced by individuals with diabetes, as well as an indirect effect mediated by self-management, with PR acting as a moderating factor. These findings suggest that healthcare practitioners should prioritize the enhancement of empowerment-based education and implement tailored interventions that consider patients’ varying levels of PR, in order to reduce stigma and promote better mental health outcomes.